Data analytics made easy : use machine learning and data storytelling in your work without writing... any code. - Mauro, Andrea de (Packt Publishing Limited, 2021)
This book takes away the fear of working with, analyzing, and visualizing data. Understand the key concepts involved with data analytics while working with real-world business examples. You are introduced to two fantastic tools to cleanse and analyze data (KNIME) and visualize your insights (Microsoft Power BI), but the principles from this ...